Energy-Efficient Retrofit of Heat Exchange Networks for Oil Treatment and Stabilization Units at Oil Fields; Energies; Vol. 19, iss. 3 - Kalybaeva B. T. Botagoz Tleugabylovna; Khusanov A. Alisher; Uljev (Ulyev) L. M. Leonid Mikhaylovich; Kenzhebekov D. Doskhan; Dzhanabaev D. Dauren; Chernyshov M. N. Mikhail Nikolaevich (2026, 2026)
Title screen